Kidney transcriptome and cystic kidney disease genes in zebrafish - Koslow, Matthew; Zhu, Ping; McCabe, Chantal; Xu, Xiaolei; Lin, Xueying (Frontiers in Physiology, 2023)
Polycystic kidney disease (PKD) is a condition where fluid filled cysts form on the kidney which leads to overall renal failure. Zebrafish has been recently adapted to study PKD, because of its powerful embryology and genetics. However, there are concerns on the conservation of this lower vertebrate in modeling PKD. Here, we aim to assess the molecular conservation of zebrafish by searching homologues PKD genes and carrying transcriptome studies in this animal. We found that out of 82 human cystic kidney disease genes, 81 have corresponding zebrafish homologs. While 75 of the genes have a single homologue, only 6 of these genes have two homologs. Comparison of the expression level of the transcripts enabled us to identify one homolog over the other homolog with >70% predominance, which would be prioritized for future experimental studies. Prompted by sexual dimorphism in human and rodent kidneys, we studied transcriptome between different sexes and noted significant differences in male vs female zebrafish, indicating that sex dimorphism also occurs in zebrafish. Comparison between zebrafish and mouse identified 10% shared genes and 38% shared signaling pathways. String analysis revealed a cluster of genes differentially expressed in male vs female zebrafish kidneys. In summary, this report demonstrated remarkable molecular conservation, supporting zebrafish as a useful animal model for cystic kidney disease.